Predictors of response to foot orthoses and corticosteroid injection for plantar heel pain - Glen A. Whittaker; Karl B. Landorf; Shannon E. Munteanu; Hylton B. Menz (Journal of Foot and Ankle Research, 2020)
Abstract Background Foot orthoses and corticosteroid injection are common interventions used for plantar heel pain, however few studies have investigated the variables that predict response to these interventions. Methods Baseline variables (age, weight, height, body mass index (BMI), sex, education, foot pain, foot function, fear-avoidance beliefs and feelings, foot posture, weightbearing ankle dorsiflexion, plantar fascia thickness, and treatment preference) from a randomised trial in which participants received either foot orthoses or corticosteroid injection were used to predict change in the Foot Health Status Questionnaire foot pain and foot function subscales, and first-step pain measured using a visual analogue scale. Multivariable linear regression models were generated for different dependent variables (i.e. foot pain, foot function and first-step pain), for each intervention (i.e. foot orthoses and corticosteroid injection), and at different timepoints (i.e. weeks 4 and 12). Results For foot orthoses at week 4, greater ankle dorsiflexion with the knee extended predicted reduction in foot pain (adjusted R 2 = 0.16, p = 0.034), and lower fear-avoidance beliefs and feelings predicted improvement in foot function (adjusted R 2 = 0.43, p = 0.001). At week 12, lower BMI predicted reduction in foot pain (adjusted R 2 = 0.33, p < 0.001), improvement in foot function (adjusted R 2 = 0.37, p < 0.001) and reduction in first-step pain (adjusted R 2 0.19, p = 0.011). For corticosteroid injection at week 4, there were no significant predictors for change in foot pain or foot function. At week 12, less weightbearing hours predicted reduction in foot pain (adjusted R 2 = 0.25, p = 0.004) and lower baseline foot pain predicted improvement in foot function (adjusted R 2 = 0.38, p < 0.001). Conclusions People with plantar heel pain who use foot orthoses experience reduced foot pain if they have greater ankle dorsiflexion and lower BMI, while they experience improved foot function if they have lower fear-avoidance beliefs and lower BMI. People who receive a corticosteroid injection experience reduced foot pain if they weightbear for fewer hours, while they experience improved foot function if they have less baseline foot pain.